Theory and empirics of capability accumulation: Implications for macroeconomic modelling - Matthias Aistleitner; Claudius Gräbner; Anna Hornykewycz (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2020)
The accumulation of new technological capabilities is of high empirical relevance, both for the development of countries and the business success of firms. In this paper, we aim to delineate strategies how these processes of capability accumulation can be considered more accurately in comprehensive macroeconomic models. To this end, we conduct an interdisciplinary review of the literature specialized on capability accumulation by analyzing both empirical as well as theoretical literature on the firm and aggregated level. In doing so, we collect evidence various determinants and mechanisms of capability accumulation and align them with the current representation of capability accumulation in macroeconomic models. Based on these results, we make some suggestions on how macroeconomists may integrate these determinants derived from the specialized literature into their models.
Keywords: 330; Capability accumulation; complexity; economic development; innovation; technological change; agent-based modeling; endogeneous growth; knowledge accumulation and learning